Inner dan Outer Space dalam Kontroversi “Salib” pada Ornamen 75 Tahun Kemerdekaan - Dien Yudithadewi; Bonifasius Parikesit (Jurnal Komunikasi, 2020)
This paper focuses on finding out what meaning is reflected in the phenomenon of rejection of ornamental design of the 75th Anniversary of Indonesia's Independence, from the perspective of Yuri Lotman's (Tartu-Moscow-Semiotic School) cultural semiotics. This ornament has become a polemic in society, because a group of people feels that there is a visual cross in it, which is a representation of a certain group. The research finding states that rejection of the ornamental design for the 75th anniversary of the Republic of Indonesia occurred because a group of people felt that the “sign” in the design represented a certain group, outside them. This opinion is described by Yuri Lotman as the concept of "the inner space" (we/us) and "the outer space" (them). According to him, each culture has boundaries for defining itself (Semenenko, 2012). Everything outside "us" is "not our culture" (non-culture) or "foreign" (alien), and is often considered not good because it is not "like us" (Lorusso, 2015).